Genetic resistance to Ceratocystis fimbriata in elite genotypes of Gmelina arborea - Méndez-Álvarez, Dawa (2023)
Introduction. In Costa Rica, an incidence of nearly 40 % has been reported for a disease caused by Ceratocystis fimbriata in commercial plantations of Gmelina arborea (melina), which is the second most widely planted forest tree species in the country. Consequently, there is a pressing need to explore genetic material that exhibit resistance to this pathogen. Objective. To evaluate two methods of C. fimbriata inoculation and their effect on elite genotypes of melina, for their use within the melina genetic improvement program at the international forest genetic improvement cooperative GENFORES. Materials and methods. A pathogenicity test was established using the CIF 001 isolate of C. fimbriata under greenhouse conditions, in Santa Clara, San Carlos, Costa Rica. Two inoculation methods were evaluated in five elite genotypes from October 2019 to January 2020. The effect of the pathogen was evaluated by measuring total height development, basal diameter, number of leaves, incidence, and internal injury within the plant. The assessment was conducted at 30, 60, 90, and 120 days. Results. Mortality was observed from day 38 and reached an incidence of 26.7 % at 120 days. The treatment using solid medium displayed the highest incidence percentage. Genotypes 15N and 58 exhibited high susceptibility to the CIF 001 isolate, whereas genotypes 1 and 57 exhibited high tolerance. Based on the results, it was determined that the pathogenicity test of C. fimbriata on melina can be evaluated at 90 days. Conclusion.  Solid medium was the most effective method for inoculating melina with C. fimbriata (isolate CIF 001). Evaluations showed the need to assess results at least 90 days after inoculation. Based on the analysis of the internal lesion, genotype 1 was identified as highly resistant to the effect of the pathogen. The inclusion of this genotype as an evaluation technique will substantially enhance the protocol for assessing tolerance to the pathogen.